The Determinants of Health Consultation Utilization among HIV Patients at Budi Kemuliaan Hospital, Batam, Indonesia - Dawiyah Siregar; Juanita Juanita; R. Kintoko Rochadi (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: HIV and AIDS is a global public health problem. Until the end of 2016, there were more than 36.7 million people living with HIV. HIV & AIDS counseling is a confidential communication between clients and counselors aimed at increasing the ability to deal with stress and make decisions regarding HIV & AIDS. The purpose of this study was to determine the effect of the ability to pay and the environmental factor on consultation health service utilization at Budi Kemuliaan hospital, Batam.Subjects and Method: This was a cross-sectional study was conducted at Budi Kemuliaan Hospital, Batam, from May 8 to June 18, 2018. A sample of 76 HIV patients was selected by systematic random sampling. The dependent variable was the use of consulting service. The independent variables were risk of illness and environment. The data were collected using questionnaires and analyzed by a multiple logistic regression.Results: The use of consultation health service was influenced by the risk of illness (OR = 6.82; p = 0.011) and supportive environment (OR= 4.59; p= 0.028).Conclusions: The use of consultation services is influenced by risk factors for illness and the environment.Keywords: consultation service, the risk of illness, environment, HIV/AIDS patientCorrespondence: